PSYCHOLOGICAL DEPICTIONS OF WOMEN IN MANOHAR MALGONKAR'S WRITINGS: A FEMINIST ANALYSIS - Priyadarshini, Sahana (ShodhKosh: Journal of Visual and Performing Arts, 2023)
A feminist approach is used in this research paper to scrutinize the psychology of women as articulated in the writings of Manohar Malgonkar while displaying the complexity in the characterizations of women in Malgonkar's stories and the challenge experienced by women in a patriarchal society. Indeed, by identifying and incorporating core themes of autonomy, resistance, and intersectionality in key novels like A Bend in the Ganges and The Princes, the research insists on the emotional, intellectual, and social components of Malgonkar's characters. This biography highlights how Malgonkar acts as a bridge between conventional and progressive portrayals of female characters in her time vis a vis modern Indian English writers she influenced and how she wrote feminist stories that foreshadowed the future of Indian writing in the language. By positioning Malgonkar as an author whose perspective on womanhood emerges before the contemporary landscape of Indian woman writers, ending with a call to consider both feminist and psychological elements in characters across narratives, the study offers new routes for delving into his writings.